Prevalence and Management of Immediate Adverse Reactions to Chemotherapy in Breast Cancer Patients: A Retrospective Study - Insfran, Guillermo; Bernal, Sandra; Ovelar, Skarlette; Pérez, Marian (Brazilian Journal of Oncology, 2025)
To analyze the prevalence, characteristics, and management of immediate adverse reactions (ARs) to chemotherapeutic agents in breast cancer patients treated at the National Cancer Institute (Instituto Nacional del Cáncer, INCAN, in Spanish) in Paraguay.A retrospective, observational, and cross-sectional study was conducted using clinical records of 200 breast cancer patients aged between 25 and 75 years submitted to outpatient chemotherapy at the INCAN between August 2022 and August 2023. The data collected included patient demographics, breast cancer subtype, chemotherapeutic agents used, and reported ARs.Descriptive statistics were used to summarize the data. Chi-square tests were performed to evaluate the associations between ARs and specific chemotherapy agents, with statistical significance set at p < 0.05.Among the 200 patients included, 61% (122/200) experienced ARs. The most common reactions were skin rash (17.1%), nausea (16.1%), and flushing (9.5%). Luminal A was the most prevalent breast cancer subtype (32.5%). Paclitaxel and docetaxel were the most frequently associated agents (29% each), but no statistically significant association was found involving specific drugs and ARs. The medications most commonly used in the management of ARs included chlorpheniramine (32%), dexamethasone (24%), and ondansetron (14%).Immediate ARs to chemotherapy are common among breast cancer patients, and they require effective monitoring and management protocols. These findings highlight the need for tailored strategies to mitigate ARs and improve treatment outcomes, particularly in resource-constrained settings.
Keywords: antineoplastic agents; drug-related side effects and adverse reactions; breast neoplasms; taxanes; hypersensitivity